Reflecting on the Science of Climate Tipping Points to Inform and Assist Policy Making and Address the Risks they Pose to Society - T. F. Stocker; R. G. Jones; M. I. Hegglin; T. M. Lenton; G. C. Hegerl; S. I. Seneviratne; N. van der Wel; R. A. Wood (Surveys in Geophysics, 2025)
There is a diverging perception of climate tipping points, abrupt changes and surprises in the scientific community and the public. While such dynamics have been observed in the past, e.g., frequent reductions of the Atlantic meridional overturning circulation during the last ice age, or ice sheet collapses, tipping points might also be a possibility in an anthropogenically perturbed climate. In this context, high impact—low likelihood events, both in the physical realm as well as in ecosystems, will be potentially dangerous. Here we argue that a formalized assessment of the state of science is needed in order to establish a consensus on this issue and to reconcile diverging views. This has been the approach taken by the Intergovernmental Panel on Climate Change (IPCC). Since 1990, the IPCC has consistently generated robust consensus on several complex issues, ranging from the detection and attribution of climate change, the global carbon budget and climate sensitivity, to the projection of extreme events and their impact. Here, we suggest that a scientific assessment on tipping points, conducted collaboratively by the IPCC and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, would represent an ambitious yet necessary goal to be accomplished within the next decade.

The influence of regional circulation patterns on wet and dry mineral dust and sea salt deposition over Greenland - M. A. Hutterli; T. Crueger; H. Fischer; K. K. Andersen; C. C. Raible; T. F. Stocker; M. L. Siggaard-Andersen; J. R. McConnell; R. C. Bales; J. F. Burkhart (Climate Dynamics, 2007)

Extreme midlatitude cyclones and their implications for precipitation and wind speed extremes in simulations of the Maunder Minimum versus present day conditions - C. C. Raible; M. Yoshimori; T. F. Stocker; C. Casty (Climate Dynamics, 2007)

Probabilistic climate change projections using neural networks - R. Knutti; T. F. Stocker; F. Joos; G.-K. Plattner (Climate Dynamics, 2003)

Constraining temperature variations over the last millennium by comparing simulated and observed atmospheric CO2 - S. Gerber; F. Joos; P. Brügger; T. Stocker; M. Mann; S. Sitch; M. Scholze (Climate Dynamics, 2003)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Abrupt climate changes: from the past to the future - a review - T. F. Stocker (International Journal of Earth Sciences, 1999)

Modelling the concentration of atmospheric CO 2 during the Younger Dryas climate event - O. Marchal; T. F. Stocker; F. Joos; A. Indermühle; T. Blunier; J. Tschumi (Climate Dynamics, 1999)

Intermittent convection, mixed boundary conditions and the stability of the thermohaline circulation - J. Hirschi; J. Sander; T. F. Stocker (Climate Dynamics, 1999)

Thiopental and midazolam do not seem to impede metabolism of glutamate in brain-injured patients - John F. Stover; Ulrike E. Pleines; Maria C. Morganti-Kossmann; Reto Stocker; Oliver S. Kempski; T. Kossmann (Psychopharmacology, 1999)